2020
DOI: 10.1002/ptr.6955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quercetin supplementation on inflammatory factors and quality of life in post‐myocardial infarction patients: A double blind, placebo‐controlled, randomized clinical trial

Abstract: Myocardial infarction (MI) is one of the leading causes of death in the world. Epidemiological studies have shown that dietary flavonoids are inversely related to cardiovascular morbidity and mortality. The study aimed to determine whether quercetin supplementation can improve inflammatory factors, total antioxidant capacity (TAC) and quality of life (QOL) in patients following MI. This randomized double‐blind, placebo‐controlled trial was conducted on 88 post‐MI patients. Participants were randomly assigned i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…There are many components of MGSD, and network pharmacological analysis confirmed that the top three TCM monomer molecules are quercetin, kaempferol and isoflavone (our unpublished data). Quercetin has been reported to treat myocardial infarction in a clinic trial (26). Kaempferol is also the active ingredient of ginkgo biloba, detecting the level of kaempferol in urine could reflect the intake of ginkgo biloba (27).…”
Section: Discussionmentioning
confidence: 99%
“…There are many components of MGSD, and network pharmacological analysis confirmed that the top three TCM monomer molecules are quercetin, kaempferol and isoflavone (our unpublished data). Quercetin has been reported to treat myocardial infarction in a clinic trial (26). Kaempferol is also the active ingredient of ginkgo biloba, detecting the level of kaempferol in urine could reflect the intake of ginkgo biloba (27).…”
Section: Discussionmentioning
confidence: 99%
“…Research showed that quercetin modulated AMPK/SIRT1/NF-κB signaling pathway [37] or JAK2/STAT3 pathway [38] to inhibit cell apoptosis and oxidative stress, reduce myocardial infarction size, improve ventricular remodeling and cardiac functionrelated biochemical indexes, and promote the recovery of cardiac blood ow. And a double-blind, placebocontrolled, randomized clinical trial demonstrated signi cantly elevated total antioxidant capacity [39]. Both two studies provided evidence for WYS treating CHD successfully.…”
Section: Analysis Of Active Ingredientsmentioning
confidence: 87%
“…Many studies have reported on the health benefits of herbs and plants including different cardamom cultivars in terms of their antioxidant, antimicrobial, and hypolipidemic potentials and potential for food applications such as functional additives ( Deepa et al, 2013 ; Abdullah et al, 2017 , 2020 ; Aghasi et al, 2019 ; Dehghani et al, 2020 ). In the healthcare and pharmaceutical industries, interest in plant-derived bioactive compounds (phytochemicals) as potential medicines has attracted the attention of researchers due to their health-promoting characteristics, such as their antioxidant, antimicrobial, anti-ulcer (gastro-protective), anti-thrombotic, and anti-hypertensive effects ( Verma et al, 2009 ; Sharma et al, 2011 ; Chakraborty et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interest in the application of bioactive phytochemicals and essential oils in food and pharmaceutical products has rapidly increased due to their health benefits, including their antioxidant, antimicrobial, and hypolipidemic properties ( Deepa et al, 2013 ; Aghasi et al, 2019 ; Yousefi et al, 2019 ; Abdullah et al, 2020 ; Dehghani et al, 2020 ). A wide variety of herbs and spices have been used in cooking and medicine, particularly in the treatment of gastrointestinal disorders, since ancient times.…”
Section: Introductionmentioning
confidence: 99%